Cluster vs. traditional training programmes: changes in the force-velocity relationship - Rial-Vázquez, J.; Mayo, X.; Tufano, J. J.; Fariñas, J.; Rúa-Alonso, M.; Iglesias-Soler, E. (Sports Biomechanics, 2022)
This randomised controlled study examined the force-velocity relationship changes (force and velocity axis intercepts, slope and estimated maximum power) in response to 5-week training programmes differing in the set configuration. For each session, the traditional group performed 4 sets of 8 repetitions with 5 min of rest between sets and exercises, while the cluster group completed 16 sets of 2 repetitions with 1 min of rest between sets and 5 min between exercises. Both programmes were performed with the 10-repetition maximum load, including bench press, parallel squat, lat pull-down and leg curl exercises. Individual force-velocity profiles were obtained for bench press and squat using a linear velocity transducer before and after the intervention, along with lactate and mechanical performance during the intervention. Results showed in bench press similar changes of the force-velocity profile after both protocols (no shift of the slope and higher force and velocity axis intercept values). For the squat, significant changes in the slope (P = 0.001) and the velocity intercept (P = 0.002) towards a velocity profile were observed after cluster but not after traditional training. These results suggest that set configuration may modulate changes of force-velocity relationship, especially for squat.